Static balloon atrial septostomy in Japan in shortage of standard balloon septostomy catheter. Issue 3 (September 2021) - Baba, Kenji; Suda, Kenji; Takamuro, Motoki; Takahashi, Shin; Sugiyama, Hisashi; Fujimoto, Kazuto; Kitano, Masataka; Fujii, Takanari; Kise, Hiroaki; Ohtsuki, Sinichi; Tomita, Hideshi
Highlights: A questionnaire survey of balloon atrial septostomy (BAS) in Japan was conducted. In Japan, the BAS catheter supply has been discontinued due to its recall. Static BAS is widely done despite being off-label in Japan and is effective and safe. Static BAS cases increased by over 90% due to a shortage of BAS catheter. An adequate supply of the BAS catheter, such as Z-5, is indispensable in Japan. Abstract: Background: The supply of Rashkind balloon atrial septostomy (BAS) catheters (Medtronic, Minneapolis, MN, USA) has suddenly been discontinued in the world due to its recall. Consequently, Japan fell into a critical shortage of standard BAS catheters. Although the use of static BAS is off-label in Japan, its importance is increasing in such a situation. A nationwide survey of static BAS is needed in such a critical period. Methods: A questionnaire survey was conducted among centers in Japan regarding BAS performed between October 1, 2020, and December 15, 2020, while the supply of Rashkind BAS catheter was discontinued. Results: We received answers from 70 of the 90 centers, for a response rate of 78%. In this survey, 25 patients who underwent static BAS were enrolled, and a total of 47 BAS procedures were performed. Median age and weight at static BAS were 10 days of life and 3001 g, respectively. The most common diagnosis was transposition of the great arteries without pulmonary stenosis and hypoplastic left heart syndrome and its variants, with 8 cases each. The most frequently used balloon diameter was 10 mm (13 balloons), followed by 12 mm (10 balloons), and 3 cases required double-balloon techniques. The 3-point scale of the efficacy of static BAS rated by physicians were 10 excellent, 15 good, and 0 poor, respectively. Complications included cardiac tamponade during the procedure in 1 patient and the need for Rashkind BAS later in 2 patients. Comparing the share of static BAS in all transcatheter atrial septostomy, its share in the current survey (28/53) is significantly higher compared to the annual registry data in 2018 (86/304) ( p  < 0.01). Conclusions: This survey shows that static BAS is widely performed in Japan and is effective and safe. Static BAS cases have increased significantly due to a shortage of standard BAS catheters.